UPAYA MENINGKATKAN PROFESIONALISME GURU IPS - Herman man man (Jurnal Ilmu Pengetahuan Sosial, 2013)
This study aims to ( 1 ) To obtain an overview of the efforts made to improve the professionalism of teachers in social studies education subjects in SMP Negeri 3 Marioriawa Soppeng ; ( 2 ) To know what supporting factors and obstacles facing social studies education teachers in improving their professionalism in SMP Negeri 3 Marioriawa Soppeng . This research is a qualitative descriptive study . Data was collected by interview , dokumentai , and observation . The population at the same time the study sample was a social studies teacher at SMP Negeri 3 Marioriawa Soppeng by 3 people .The results showed that the effort to increase the professionalism of a social studies teacher at SMP Negeri 3 Marioriawa Soppeng include delivery PLPG teachers in activities and also MGMPs regularly , as well as classroom visits and school visits on a regular basis and the application of the four competencies are pedagogical, personality , professional and social already well underway . This is evidenced by the achievement of effective and efficient learning .Factors that inhibit in improving the professionalism of teachers in SMP Negeri 3 Marioriawa ie , facilities and infrastructure owned by SMP 3 Marioriawa Soppeng still include less because there are laboatorium ips insufficient and inadequate financing . As a contributing factor in improving the professionalism of social studies teachers in SMP Negeri 3 Marioriawa is , teacher welfare ( salary increases ) certification benefits , and awards , such as outstanding teachers or teacher discipline